The KAP-Gap in Nepal: Reasons for non-use of contraception among couples with an unmet need for family planning - Ashoke Shrestha; John Stoeckel; Jayanti Man Tuladhar (Asia-Pacific Population Journal, 1991)
Fertility and family planning surveys conducted in developing countries around the world have consistently reported an inverse relationship between fertility preferences and the practice of contraception. These surveys have also shown, however, that substantial proportions of women stating that they do not want any more children are not practising contraception. These proportions generally range from 25 to 50 per cent, and reach even higher levels in Africa. This discrepancy between women’s stated preference to have no more children and their non-use of contraception is euphemistically referred to as the “KAP-Gap”.